Respiratory physiology: stay @ home Challenge - Abdul Ghani, Radiah; Ikmal Hisham, Ahmad Irfan (2022)
Delivering effective laboratory experience in science is challenging to do remotely. The expensive and nonportable nature of laboratory equipment makes it challenging to replicate the experiment in a remote learning environment. However, the COVID-19 era changed the perception where the capability of learning the concept is possible through the home-based learning approach. To assist the student to learn the concept in physiology remotely, a self-instructional module was designed with the aim to teach the students how to do hypothesis-driven physiology experiments with inexpensive and flexible choice of materials. Students received the instructional module which has been validated named Respiratory: Stay @Home Challenge. This module has two activities in which students need to complete using available materials at home and internet resources. The students were given one week to complete the task and the evidence and report need to be submitted via google form. A questionnaire to evaluate the knowledge on respiratory systems was given during pre and post activities. The qualitative evaluation was conducted to identify their perception. A significant improvement in knowledge was found among the subjects (p<0.01). Also a statistically significant difference was found for QOL scores in post-intervention. The home-based activities during pandemic were found to effectively improve the knowledge and understanding on the concept in physiology. Hence, the home-based activities should be considered as an alternative mode for laboratory experiment during pandemic crisis in future.